2017
DOI: 10.1136/gutjnl-2017-314205
|View full text |Cite
|
Sign up to set email alerts
|

Gastric microbial community profiling reveals a dysbiotic cancer-associated microbiota

Abstract: ObjectiveGastric carcinoma development is triggered by Helicobacter pylori. Chronic H. pylori infection leads to reduced acid secretion, which may allow the growth of a different gastric bacterial community. This change in the microbiome may increase aggression to the gastric mucosa and contribute to malignancy. Our aim was to evaluate the composition of the gastric microbiota in chronic gastritis and in gastric carcinoma.DesignThe gastric microbiota was retrospectively investigated in 54 patients with gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
559
10
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 494 publications
(646 citation statements)
references
References 44 publications
(42 reference statements)
43
559
10
8
Order By: Relevance
“…Increased diversity (richness and phylogenetic diversity;) or no differences (evenness and Shannon; in cancer in comparison with patients with functional dyspepsia or chronic gastritis were noted. However, the two studies with the largest patient numbers reported decreased diversity in cancer or intestinal metaplasia in comparison with the chronic gastritis microbiota. The gastric microbial community profiles in cancer were significantly different from those of noncancerous stomachs .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Increased diversity (richness and phylogenetic diversity;) or no differences (evenness and Shannon; in cancer in comparison with patients with functional dyspepsia or chronic gastritis were noted. However, the two studies with the largest patient numbers reported decreased diversity in cancer or intestinal metaplasia in comparison with the chronic gastritis microbiota. The gastric microbial community profiles in cancer were significantly different from those of noncancerous stomachs .…”
Section: Resultsmentioning
confidence: 94%
“…Specific microbial groups were rarely found exclusively in one diagnostic group. For instance, a Portuguese cohort of gastric cancer compared to gastritis patients showed that cancer patients had increased abundance of several microbial groups including Achromobacter . However, Achromobacter species were completely absent in a Chinese validation cohort, indicating that geographical origin might have similar if not stronger impact on the gastric microbiota composition than the pathology itself.…”
Section: Resultsmentioning
confidence: 99%
“…However, analysis of cancer‐specific enrichment and depletion at the taxonomic level yielded conflicting results between the two studies, possibly reflecting different geographic, ethnic and dietary backgrounds of the study populations. Furthermore, comparing the study results with the PPI‐associated changes to the gastric microbiota reviewed here, not a single concordantly regulated taxon can be identified …”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenesis of gastric cancers is associated with H. pylori and some oral microbiota including Fn , Parvimonas micra and Peptostreptococcus stomatis . Significant enrichment of Peptostreptococcus stomatis , Parvimonas micra , Streptococcus anginosus , Dialister pneumosintes , Slackia exigua, Clostridium colicanis and Fn and depletion of Helicobacterium was observed in gastric cancer, and alterations in bacterial diversity and abundance in patients with gastric cancer revealed a dysbiotic microbial community with prediction potential . Recently, incremental data has demonstrated that eradication treatment for H. pylori could reduce the risk of gastric cancer .…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%